Management Compensation, Financial Distress, Accounting Conservatism, Sales Growth on Tax Avoidance with Audit Quality as Moderating Variable - Joshua Julianta; Binsar H Simanjuntak (Budapest International Research and Critics University, 2023)
This study investigates the effect of management compensation, financial distress, accounting conservatism and sales growth on tax avoidance with auditor quality as moderating variable. Sample consist of 54 manufacturing firm that list on LQ 45 Indonesian Stock Exchange during 2019-2021. This study used regression analysis to test the hypotheses. The finding suggests that management compensation and accounting conservatism have a positive effect on tax avoidance. Financial distress and sales growth had no effect on tax avoidance. Audit quality strengthens the effect of sales growth on tax avoidance, but audit quality can not moderate the effect of management compensation, financial distress and accounting conservatism on tax avoidance.